Comparisons of the Codex Alimentarius Principles of Nutrition Labelling and Relevant Guidelines of Taiwan and the United States - Chiang, I-Yuan (Open textbook library., 2022)
Codex Guidelines on Nutrition Labelling and The US 21 CFR PART 101.9 Nutrition Labeling are the primary references for Taiwan FDA to establish and amend the nutrition labeling regulations. In January 2022, Codex updated the Guidelines on Nutrition Labelling. We finished the translation in April and integrated the related regulations from Taiwan and the US into this book. The expected audiences include food manufacturers in the international food trade and college students in food and nutrition majors. We hope the bilingual book can provide a general framework for the readers.